Leisure cultures in urban Europe, c.1700-1870 : A transnational perspective - Furnee, Jan Hein; Borsay, Peter (Book collections on Project MUSE., 2016)
This volume combines research on a wide variety of leisure activities in the early modern and modern periods, providing an unprecedented transnational perspective to the study of European leisure history.